Mediastinite Descendante Necrosante Aigue: Quatre Annees D’experience Dans Un Centre Hospitalier A Madagascar - Razafimanjato, Narindra Njarasoa Mihaja; Ralaizafindraibe, Tojomamy Herinjaka; Ramarolahy, Andriatiarainy Rija; Rajaonera, Tovo Andriambelo; Rakotovao, Jean Louis Hanitrala (European Scientific Journal, ESJ, 2017)
Background: The acute mediastinitis also called Descending Necrotizing Mediastinitis or Cervico-mediastinitis necrotizing fasciitis is a disease which is the result of a spread of severe cervical infection down to the mediastinum. Method: A retrospective study was done at the surgical intensive care unit of Joseph Ravoahangy Andrianavalona’s hospital about the management of descending necrotizing mediastinitis from 1 st January 2009 to 31st December 2012. Result: Fourteen cases were reported during four years. The mean age of the patients was 30 years and 8 months, the sex ratio was 1.33. The most common cause found in every cases were severe cervical infections such as fasciitis by dental origin, peritonsillar abcess, sore throat, combined with the administration of non steroid antiinflammatory, of corticoid, of inappropriate antibiotic and also the patients’ health status. The suspicion of diagnosis is made clinically with chest pain associated with dyspnea, fever or septic shock and confirmed by radiologic findings. Conclusion: Nowadays, the mortality rates is high about 71, 42% for our cases. Collaboration of the thoracic surgeons and anesthetists is recommended for an early trancervical drainage of the mediastinitis. In Madagascar, the fasciitis by odontogenic infection is the most common cause of mediastinitis due to the lack of dental care.